2014
DOI: 10.1007/s10616-014-9813-1
|View full text |Cite
|
Sign up to set email alerts
|

NT-3 attenuates the growth of human neuron cells through the ERK pathway

Abstract: Spinal cord injury is a devastating health problem that affects thousands of individuals each year. The neurons were destroyed. NT-3 is a recently discovered neurotrophin. This study sought to understand the potential involvement of MAPKs in NT-3-mediated growth inhibition of human neurons. We applied different concentrations of NT-3 and observed the growth rate of the cells and the changes in the phosphorylation state of the MAPKs ERK1/2, JNK and p38. This study discovered that NT-3-induced HNC growth was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…ERK and Akt played an important role in cell proliferation, apoptosis, migration and staying cell morphology. ERK and Akt were activated through phosphorylating tyr202/204 and ser473 residues, respectively, and exerted their functions [ 20 , 21 ]. We evaluated the expression levels of total ERK and p-ERK by Western blot after treated with AT-II for 48 h. The activation level of ERK was downregulated significantly by AT-II in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…ERK and Akt played an important role in cell proliferation, apoptosis, migration and staying cell morphology. ERK and Akt were activated through phosphorylating tyr202/204 and ser473 residues, respectively, and exerted their functions [ 20 , 21 ]. We evaluated the expression levels of total ERK and p-ERK by Western blot after treated with AT-II for 48 h. The activation level of ERK was downregulated significantly by AT-II in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that NT-3 binds to TrkC, triggers the receptor and signals cascades (Ivanov et al 2013;Han et al 2016;Li et al 2016). To identify the signaling pathway through which NT-3 on 661W cells, cells were treated with exogenous NT-3 (20 nM) for 24 h and the phosphorylation state of the mitogenactivated protein kinase (MAPK) signaling pathway was examined, including ERK1/2, p38 and JNK.…”
Section: Nt-3 Inhibited the Apoptosis Of 661w Cells Via Erk1/2 Pathwaymentioning
confidence: 99%
“…Impaired ERK Activation in Pyramidal mPFC-IL Neurons of TgNTRK3 Mice ERK activation, which can be triggered by the NT3/TrkC intracellular signaling cascade (Li et al, 2014;Reichardt, 2006), is necessary for successful fear extinction in rodents (Fischer et al, 2007;Tronson et al, 2009). We therefore reasoned that altered NT3/TrkC function might disturb fear extinction memory in TgNTRK3 mice due to impaired ERK signaling.…”
Section: Acquisition Of Contextual Fear Conditioning and Extinction Rmentioning
confidence: 99%
“…First, we observed that TgNTRK3 did not show the extinction-related increase in NT3 levels in the mPFC that we observed in WT animals. Binding of NT3 to its highaffinity TrkC receptor results in intracellular activation of ERK signaling (Li et al, 2014;Reichardt, 2006). Therefore, the NT3 deficit observed in TgNTRK3 animals is likely to result in a deficit in the activation of the NT3/TrkC downstream pathway ERK.…”
Section: Impaired Fear Extinction Rescue Via Nt3/trkc-erk Pathway D Dmentioning
confidence: 99%